UNIT 4.31 Fluorescent Detection of Lipid Droplets and Associated Proteins. Issue 1 (1st June 2016) - Listenberger, Laura L.; Studer, Andrea M.; Brown, Deborah A.; Wolins, Nathan E.
Abstract : Excess lipid is stored in intracellular organelles known as lipid droplets. This unit discusses techniques for the visualization of lipid droplets and associated proteins in cultured mammalian cells. Protocols for the detection of lipid droplets in fixed or live cells with BODIPY 493/503 are included. The best method for combining visualization of intracellular lipid droplets with indirect immunofluorescent detection of lipid droplet–associated proteins is described. Techniques for sample fixation and permeabilization must be chosen carefully to avoid alterations to lipid droplet morphology. Immunofluorescent detection of perilipin 2, a broadly expressed, lipid droplet–associated protein, widely used as a marker for lipid droplet accumulation, is presented as an example. Finally, a simple protocol for enhancing lipid droplet accumulation through supplementation with excess fatty acid is included. © 2016 by John Wiley & Sons, Inc.